Legal Aspects of the Concept of a Brand with a Domain Name of Intellectual Property - Nurpalah, Nurpalah; Senjaya, Oci (Universitas Islam Lamongan, 2023)
This is a problem in itself considering that domain names, which technically function as online identifiers used to make it easier to find certain locations in cyberspace, are often associated with brands that are actually business identifiers in the real world. The purpose of this study is to determine the linkage, protection, and settlement for brand owners whose brands are registered as domain names by other parties in the context of Indonesian law. The method used in this research is a normative legal research method with a statutory, case, and concept approach. However, the result of this research is that brands and domain names have a common function as a